Numerical Simulation of Grab Dredging on Flow Field and Sdiment Suspension Pattern in Construction Area - LONG Rui, JIN Zhong-wu, Tomoaki NAKAMURA, Yonghwan CHO, Norimi MIZUTANI (长江科学院院报)
[Objectives] The sedimentation of rivers and lakes poses a persistent challenge to water resource management. Dredging, while effective for removing excess sediment and restoring channel capacity, often triggers the resuspension of contaminated bed material, leading to secondary pollution and ecological disturbance. Among various dredging techniques, grab-type dredging is widely used for its adaptability to diverse bed conditions, but its impact on local flow fields and sediment dynamics remains underexplored. This study addresses this gap by employing a full-scale two-dimensional numerical simulation using the FS3M (Fluid-Structure-Sediment-Seabed Interaction Model) to investigate the hydrodynamic and sediment suspension responses during grab bucket descent. The aim is to identify descent strategies that minimize sediment resuspension and contribute to more environmentally friendly dredging operations. [Methods] The simulation framework integrates Large Eddy Simulation (LES) for turbulent flow, a Volume of Fluid (VOF) method for water-sediment interface tracking, and a sediment transport module (STM) for modeling both suspended and bedload sediment processes. A 23 m3 environmentally friendly grab bucket is modeled descending in a symmetric two-dimensional domain that includes a 3-meter-thick sand bed. Multiple descent cases are considered: a baseline with constant velocity (1.0 m/s) and six modified cases where the grab decelerates at different heights (1.0 m, 3.0 m, 5.0 m) above the bed, with secondary descent speeds of either 0.33 m/s or 0.50 m/s. Bed deformation, flow velocity, and sediment concentration distributions are monitored over time to assess each strategy’s environmental performance. [Results] Simulation results show that the grab bucket generates significant flow disturbances during its descent, especially near the sediment bed, causing bed erosion and sediment entrainment. In the baseline scenario, rapid descent leads to high flow velocities at the bed surface and the formation of vortices that promote sediment resuspension and diffusion. In contrast, cases involving velocity reduction prior to bed contact exhibit a marked decrease in sediment disturbance. Specifically: 1)Lowering the descent speed reduces the near-bed flow velocity and suppresses the entrainment of suspended sediment. 2)Starting the deceleration at 3.0 meters above the bed (Case D3) with a reduced speed of 0.33 m/s achieves the best balance between operational efficiency and environmental performance. 3)Cases with deceleration starting at 5.0 meters do not significantly improve sediment control compared to the 3.0-meter point, suggesting diminishing returns for earlier deceleration. 4)The presence of a movable bed significantly alters flow patterns compared to fixed-bed simulations, emphasizing the importance of accounting for sediment feedback in modeling. [Conclusions] This study demonstrates that modifying the descent speed of a grab bucket is an effective way to reduce sediment resuspension during dredging operations. Key conclusions are as follows: 1)Environmental Impact Mitigation: Gradually reducing the grab’s descent speed before it reaches the sediment bed effectively decreases near-bed turbulence and sediment entrainment, thereby mitigating secondary pollution. 2)Recommended Strategy: Decelerating to one-third of the initial speed (0.33 m/s) starting at 3.0 m above the bed is the optimal descent profile among the cases studied, achieving substantial reduction in suspended sediment without compromising operational feasibility. 3)Modeling Advances: The integration of fluid, structural, and sediment dynamics through the FS3M model provides a powerful tool for analyzing complex interactions in dredging scenarios, capturing realistic behavior that conventional monitoring methods cannot resolve. 4)Future Work: Further studies should extend the modeling to include sediment excavation and lifting processes, and explore dynamic descent control strategies based on real-time sediment feedback.